NEK7 Coordinates Rapid Neuroinflammation After Subarachnoid Hemorrhage in Mice - Li, Gen; Dong, Yushu; Liu, Dongdong; Zou, Zheng; Hao, Guangzhi; Gao, Xu; Pan, Pengyu; Liang, Guobiao (Frontiers in Neurology, 2020)
Background: Subarachnoid hemorrhage (SAH) is a devastating disease which leads to high morbidity and mortality. Recent studies have indicated that, never in mitosis gene A-related expressed kinase 7 (NEK7), is involved in NLRP3 (NLR family, pyrin domain containing 3) associated inflammation, which may result in subsequent cellular and vascular damage. The aim of this study was to investigate whether NEK7 is involved in the pathophysiology of subarachnoid hemorrhage. Methods: 455 adult male C57B6J mice, weighing 22 to 30 g, were used to investigate the time course of NEK7 expression in the ipsilateral cortex after SAH, and to investigate the intrinsic function and mechanism of NEK7. A vascular puncture model was used to create the mouse SAH model, and intracerebroventricular injection was used to deliver NEK7 recombinant protein, NEK7 small interfering RNA, nigericin, and MCC950. Neurological score, brain water content, Evans blue extravasation, immunofluorescence, and western blot were evaluated for neurological outcome, neuronal apoptosis, blood-brain barrier damage, microglia accumulation, and the mechanism of NEK7 and NLRP3 activation. Results: Our results exhibited that intrinsic NEK7 was elevated after SAH in the cortex of the left/ipsilateral hemisphere and was colocalized with microglia, endothelial cells, neuron, astrocyte, and oligodendrocyte, and highly expressed in microglia and endothelial cells after SAH. NEK7 recombinant protein aggravated neurological deficits, brain edema, neuronal apoptosis, BBB permeability, microglial accumulation, and activated caspase-1 and IL-1β maturation, while NEK7 small interfering RNA injection reversed those effects. Nigericin administration enhanced ASC oligomerization, caspase-1 and IL-1β maturation without increasing the protein level of NLRP3, and ASC oligomerization and caspase-1 IL-1β maturation reduced when combined with NEK7 knockdown or MCC950 delivery. We found the level of NEK7 expression increased after SAH and could activate the downstream NLRP3 pathway to induce caspase-1, IL-1β expression and then increased the BBB opening, microglia accumulation and neuronal apoptosis after SAH. Conclusions: This study demonstrated for the first time that NEK7 mediated the harmful effects of neuronal apoptosis and BBB disruption after SAH, which may potentially be mediated by the NEK7/NLRP3 signal. NEK7 served as a co-component for NLRP3 inflammasome activation after SAH. NEK7 may be a promising target on the management of SAH patients.